The role of Wnt, ARL4C, and Sema3A in developmental process and disease pathogenesis - Fujii, Shinsuke; Kiyoshima, Tamotsu (Pathology international, 2023)
Various types of tumors, including malignant and benign ones, occur in the oral cavity. These arise from the mucosal epithelium, odontogenic epithelium, and salivary gland. To date, few major driver events in oral tumors have been identified. Accordingly, molecular targets in anti‐tumor therapy for oral tumors are lacking. We focused on elucidating the function of aberrantly activated signal transduction related to oral tumor formation, especially in oral squamous cell carcinoma, ameloblastoma, and adenoid cystic carcinoma, which are raised as common oral tumors. Wnt/β‐catenin‐dependent pathway is involved in the developmental process, organ homeostasis and disease pathogenesis through regulating various cellular functions by enhancing transcriptional activity. Recently, we identified ADP‐ribosylation factor (ARF)‐like 4c (ARL4C) and Semaphorin 3A (Sema3A), the expression of which is regulated by Wnt/β‐catenin‐dependent pathway, and characterized their functions in the developmental process and tumor formation. This review highlights the recent advances in understanding the roles of Wnt/β‐catenin‐dependent pathway, ARL4C and Sema3A, as determined by pathological and experimental studies.